CIP2A expression predicts recurrences of tamoxifen-treated breast cancer. Issue 10 (October 2017) - Baldacchino, Shawn; Wastall, Laura M; Saliba, Christian; Hughes, Thomas A; Scerri, Christian; Berwick, Angelene; Speirs, Valerie; Hanby, Andrew M; Grech, Godfrey
CIP2A is emerging as an oncoprotein overexpressed commonly across many tumours and generally correlated with higher tumour grade and therapeutic resistance. CIP2A drives an oncogenic potential through inhibiting protein phosphatase 2A, stabilizing MYC, and promoting epithelial-to-mesenchymal transition, although further biological mechanisms for CIP2A are yet to be defined. CIP2A protein expression was studied by immunohistochemistry in oestrogen receptor–positive primary breast cancers (n = 250) obtained from the Leeds Tissue Bank. In total, 51 cases presented with a relapse or metastasis during adjuvant treatment with tamoxifen and were regarded as tamoxifen resistant. CIP2A expression was scored separately for cytoplasmic, nuclear, or membranous staining, and scores were tested for statistically significant relationships with clinicopathological features. Membranous CIP2A was preferentially expressed in cases who experienced a recurrence during tamoxifen treatment thus predicting a worse overall survival (log rank = 8.357, p = 0.004) and disease-free survival (log rank = 21.766, p < 0.001). Cox multivariate analysis indicates that it is an independent prognostic indicator for overall survival (hazard ratio = 4.310, p = 0.013) and disease-free survival (hazard ratio = 5.449, p = 0.002). In this study, we propose the assessment of membranous CIP2A expression as a potential novel prognostic and predictive indicator for tamoxifen resistance and recurrence within oestrogen receptor–positive breast cancer.